Investigation of the mechanism of baicalein in the treatment of periodontitis based on network pharmacology, molecular docking and experimental validation - Yue Liu; Fengdi Cao; Mingyue Shi; Zhuohang Deng; Kaili Guo; Tiantian Fan; Yuhan Meng; Mingyang Bu; Zhe Ma (BMC, 2024)
Abstract Purpose To verify the effect and mechanism of baicalein in the treatment of periodontitis through network pharmacology, molecular docking and in vitro experiments. Methods Firstly, multiple databases were used to predict targets of baicalein and periodontitis. And the screened key target genes of baicalein for treating periodontitis were subjected to GO and KEGG analysis; then these targets were analyzed by molecular docking techniques. In vitro experiments including CCK-8, RT-qPCR, ELISA and Immunofluorescence were conducted to validate the efficacy of baicalein in treating periodontitis. Results Seventeen key targets were screened from the databases, GO and KEGG analysis of these targets revealed that baicalein may exert therapeutic effects through regulating TNF, PI3K-Akt, HIF-1 and other signaling pathways. Molecular docking analysis showed that baicalein has good binding potential to several targets. In vitro cellular assays showed that baicalein inhibited the expression of TNF-α, MMP-9, IL-6 and MCP1 in P.g-LPS-induced macrophages at both the mRNA and protein level. And the immunofluorescence intensity of iNOS, a marker of M1 type macrophages, which mainly secretes inflammatory factors, was significantly reduced. Conclusion Baicalein has the characteristics and advantages of "multicomponent, multitarget, and multipathway" in the treatment of periodontitis. In vitro cellular assays further confirmed the inhibitory effect of baicalein on the secretion of inflammatory factors of macrophages in periodontitis models, providing a theoretical basis for further study of the material basis and molecular mechanism of baicalein in the treatment of periodontal diseases.